Mind the sum

Calculus Level 3

Ω = 3 3 ( log ϕ + n = 1 ( ( 2 n 1 ) ! ) 2 ( 4 n 1 ) ! ) 4 0 1 1 x 2 d x \Omega = 3\sqrt 3\left(\log\phi +\sum_{n=1}^{\infty} \dfrac{\,((2n-1)!)^2}{(4n-1)!}\right)-4\int_{0}^{1}\sqrt{1-x^2}\,dx

The value of Ω \Omega defined above can be expressed as a a ( log ϕ + b c d ln ( e a d c ) ) a\sqrt a \left(\log \phi +\dfrac{b}{c\sqrt d}\ln\left(\dfrac{e-a\sqrt d}{c}\right)\right) where the unknowns are positive integer and a , c , d , e a,c,d ,e are primes. Find the value of a + b + c + d + e a+b+c+d+e .

Source : This problem is taken from Romanian Mathematical Magazine and proposed by Prof. Daniel Sitaru .


The answer is 18.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Naren Bhandari
Feb 10, 2019

My approach

Given integral I = 4 0 1 1 x 2 d x I= 4\int_{0}^{1} \sqrt {1-x^2}\,dx represent the total area of circle of radius r = 1 r=1 . so I = π I=\pi . Also the integral can be solved by beta function.

Evaluting the sum as n = 1 ( ( 2 n 1 ) ! ) 2 ( 4 n 1 ) ! = n = 1 0 1 t 2 n 1 ( 1 t ) 2 n 1 d t = 0 1 t 2 t ( t 2 t 1 ) ( t 2 t + 1 ) d t = 1 2 0 1 ( 1 t 2 t 1 + 1 t 2 t + 1 ) d t = 1 2 0 1 ( 1 ( t 1 2 ) 2 5 4 + 1 ( t 1 2 ) 2 + 3 4 ) d t \begin{aligned} \sum_{n=1}^{\infty} \dfrac{((2n-1)!)^2}{(4n-1)!}&=\sum_{n=1}^{\infty}\int_{0}^{1} t^{2n-1}\,(1-t)^{2n-1}\,dt = \int_{0}^{1}\dfrac{t^2-t}{(t^2-t-1)(t^2-t+1)}\,dt\\& =\dfrac{1}{2} \int_{0}^{1}\left(\dfrac{1}{t^2-t-1}+\dfrac{1}{t^2-t+1}\right)\,dt\\&= \dfrac{1}{2}\int_{0}^{1}\left(\dfrac{1}{\left(t-\frac{1}{2}\right)^2-\frac{5}{4}} +\dfrac{1}{\left(t-\frac{1}{2}\right)^2+\frac{3}{4}}\right)\,dt\end{aligned} By the use of standard integration formula we have = 2 5 tan 1 ( 2 t 1 3 ) + 1 2 3 ln [ 2 t 1 5 2 t 1 + 5 ] =\dfrac{2}{\sqrt 5} \tan^{-1}\left(\dfrac{2t-1}{\sqrt 3}\right)+\dfrac{1}{2\sqrt 3}\ln\left[\dfrac{|2t-1-\sqrt 5|}{|2t-1+\sqrt 5|}\right] now setting then limits we deduce = π 3 3 + 1 2 5 ln [ 3 5 3 + 5 ] =\dfrac{\pi}{3\sqrt 3}+\dfrac{1}{2\sqrt 5}\ln\left[\dfrac{3-\sqrt 5}{3+\sqrt 5}\right] Thus Ω = 3 3 ( log ϕ + π 3 3 + 1 2 5 ln [ 3 5 3 + 5 ] ) π = 3 3 log ϕ + 3 3 2 5 ln [ 3 5 3 + 5 ] = 3 3 ( log ϕ + 1 2 5 ln [ 7 3 5 2 ] ) \begin{aligned}\Omega & = 3\sqrt 3\left(\log\phi +\dfrac{\pi}{3\sqrt 3}+\dfrac{1}{2\sqrt 5}\ln\left[\dfrac{3-\sqrt 5}{3+\sqrt 5}\right]\right) -\pi\\ & =3\sqrt 3\log \phi +\dfrac{3\sqrt 3}{2\sqrt 5}\ln\left[\dfrac{3-\sqrt 5}{3+\sqrt 5}\right]=3\sqrt 3\left(\log \phi +\dfrac{1}{2\sqrt 5}\ln\left[\dfrac{7-3\sqrt 5}{2}\right]\right)\end{aligned} gives us a + b + c + d + e = 18 a+b+c+d+e=18

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...